(untitled) (Journal of Atomic and Molecular Sciences, 2010)
The conductance of carbon atomic wire in the environment of H_2O molecules is studied by the non-equilibrium Green function method based on density functional theory. In particular, the carbon wire with seven atoms sandwiched between the Al(100) electrodes is considered. It is found that the transport properties are sensitive to the variation of the number and the position of the H_2O molecule adsorbed on the carbon wire. To our surprise, with different positions of a single H_2O molecule on the carbon wire, the equilibrium conductance shows an evident odd-even oscillatory behavior. For example, the equilibrium conductance of the carbon wire becomes bigger when the H_2O is adsorbed on the odd-numbered carbon atoms; an opposite conclusion is obtained for the H_2O adsorbed on the even-numbered carbon atoms. For the cases of two H_2O molecules, the equilibrium conductance varies largely and the contribution of the third eigenchannel becomes larger in some special configurations. The above behavior is analyzed via the charge transfer and the density of states (DOS). Reasonable explanations are presented.